Mathematics teachers and curriculum: Authors or actors? - Peralta, Deise Aparecida [UNESP]; Pacheco, José Augusto; De Lima Palanch, Wagner Barbosa (My University, 2021)
Background: Among the plurality of themes addressed by curricular studies, the nature of decision-making processes involving education professionals has guided some research agendas. Delineated by one of those agendas, this text starts by asking what the participation of teachers in processes involving curriculum is. Objective: To analyse the rationality underlying the involvement of mathematics teachers in the context of curriculum reforms in Brazil and Portugal, presenting a theoretical basis inspired by Jürgen Habermas and its suitability to discuss teachers' participation as authors or actors of curricula reforms. Design: Reconstructive analysis of rationality according to the Habermasian discursive ethics. Settings and participants: The context of a comparative study that surveys documents and interviews with two managers of a curricular reform project in Portugal and Brazil, respectively. Data collection and analysis: Analysis of the rationality that underlies the discourse present in curriculum documents of the countries involved and interviews. Results: Centralising elements of national curriculum policies do not mean by themselves the homogenisation of curricula, the rationality that underlies how projects predict the participation of teachers express an illusory discursive varnish about teachers actively participating, there are spaces of micropolicies with controlled margin of changes that advocate mathematics teachers as builders of policies, but the mechanisms of external regulation contradict this. Conclusions: Historically, in both countries, the educational systems, even expressing a rhetorical discourse on autonomy and flexibility, have remained hostages to the regulation of centralist global policies.
Professores de matemática e currículos: autores ou atores?
Keywords: Curriculum; Habermas; Mathematics teachers; Rationalities